Analysis of climatic and social performances of low cost terrace housing (LCTH) - introducing the affordable quality housing (AQH) concept in Malaysia - Abdul Majid, Noor Hanita (Archnet, Massachusettes Institute of Technology (MIT), United States, 2009)
Low cost terrace housing (LCTH) is the most common form and popular typology of public housing in Malaysia. The provision of the houses is deemed to be the most suitable to fulfill the needs to house low income families, and also as an alternative to high rise low cost housing. Since the implementation of these housing types, development on the layout and sizes of the house has taken place to provide for better living conditions. Literature review on the current LCTH suggested that there are deficiencies in fulfilling the requirements to provide quality and affordable housing for the low income families. This paper presents the scenario of the LCTH design based on secondary findings by researchers on housing in Malaysia. The secondary data provided the grounds for the proposal of affordable and quality housing (AQH) to handle the problems that occurred at the LCTH. Both social and climatic considerations are included in the AQH, addressing issues on privacy, segregation of genders and community interaction; along with thermal comfort and natural ventilation. Decisions on the AQH are carefully extracted from a comparison analysis in the view to improve the current conditions. In order to verify some of the decisions on climatic design strategies, simulation results are presented. The results indicated that the design decisions have managed to improve on the natural ventilation conditions at the low cost houses. With reservations on the social conditions that are yet to be tested at the actual houses, the AQH has proven to be a step forward towards the provision of a better living environment.